2018
DOI: 10.1186/s12986-018-0267-x
|View full text |Cite
|
Sign up to set email alerts
|

Medium-chain fatty acids decrease serum cholesterol via reduction of intestinal bile acid reabsorption in C57BL/6J mice

Abstract: BackgroundBile acids play a pivotal role in cholesterol metabolism via the enterohepatic circulation. This study investigated the effects of medium-chain triglycerides (MCTs)/medium-chain fatty acids (MCFAs) on the reduction of bile acid absorption in the small intestine and the mechanisms of action in vivo and partially verified in vitro.MethodsThirty-six C57BL/6 J mice with hypercholesterolaemia were randomly divided into 3 groups: fed a cholesterol-rich diet (CR group), fed a cholesterol-rich and medium-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 35 publications
1
19
0
2
Order By: Relevance
“…Some studies indicate that saturated fat increases the serum levels of cholesterol. However, a recent report indicates that medium chain fatty acids decrease serum cholesterol levels via reduction of bile absorption [ 36 ]. As indicated in Table 2 , major fatty acids of coconut milk are medium chain fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies indicate that saturated fat increases the serum levels of cholesterol. However, a recent report indicates that medium chain fatty acids decrease serum cholesterol levels via reduction of bile absorption [ 36 ]. As indicated in Table 2 , major fatty acids of coconut milk are medium chain fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatic bile acid synthesis genes Cyp7a1 and Cyp8b1 were significantly lower than wild-type littermates, indicating alterations in bile acid signaling. Furthermore, Li et al recently demonstrated that feeding with medium-chain fatty acids (MCFAs) reduced IBABP protein expression but not intestinal bile acid transporter expression (234). These mice showed decreased plasma LDL cholesterol levels and a decrease in bile acid absorption, suggesting that the loss of IBABP may contribute to impaired bile acid absorption.…”
Section: Ileal Bile Acid-binding Protein (Ibabp)-mentioning
confidence: 99%
“…Two medium chain length fatty acids (MCFAs), namely capric (C10:0) and caprylic (C8:0) acid, were found to promote fecal bile acid secretion through the stimulation of Cyp7a1 activity in C57BL/6J mice liver (Xu et al, 2013;Liu et al, 2017). In another independent study, the addition of capric and caprylic acid to the cholesterol-rich diet given to C57BL/6J mice resulted in high serum triglycerides level and increased fecal bile content (Li et al, 2018). Interestingly, Li et al (2018) proposed a different conclusion as they discovered the two MCFAs increased fecal bile acid through down-regulation of fatty acid-binding protein (Fabp6), a binding protein essential for reabsorption of bile acid from the small intestine.…”
Section: Mice Supplemented With Coconut Milk But Not Light Cream Haltmentioning
confidence: 99%
“…In another independent study, the addition of capric and caprylic acid to the cholesterol-rich diet given to C57BL/6J mice resulted in high serum triglycerides level and increased fecal bile content (Li et al, 2018). Interestingly, Li et al (2018) proposed a different conclusion as they discovered the two MCFAs increased fecal bile acid through down-regulation of fatty acid-binding protein (Fabp6), a binding protein essential for reabsorption of bile acid from the small intestine. Since both Cyp7a1 and Fabp6 are directly regulated by Fxr, it is reasonable to postulate that the MCFAs may act on these effectors through it.…”
Section: Mice Supplemented With Coconut Milk But Not Light Cream Haltmentioning
confidence: 99%